Chemiluminescence in the reaction of 1, 2, 4, 5-tetraoxanes with ferrous ions in the presence of xanthene dyes: fundamentals and perspectives of analytical applications. Issue 5 (13th February 2019) - Kazakov, Dmitri V.; Nazyrov, Timur I.; Safarov, Farit E.; Yaremenko, Ivan A.; Terent'ev, Alexander O.
Abstract : The reaction of biologically active bridged 1, 2, 4, 5-tetraoxanes and diperoxide of trifluoroacetone with Fe 2+ ions in the presence of xanthenes, methylene blue and methylene green is accompanied by bright chemiluminescence. Abstract : The reaction of biologically active bridged 1, 2, 4, 5-tetraoxanes and diperoxide of trifluoroacetone with ferrous ions in the presence of xanthenes, methylene blue and methylene green is accompanied by bright chemiluminescence (CL) caused by the emission from electronically-excited dyes. The promising perspectives for the employment of the CL method for the analytical detection of tetraoxanes were demonstrated. The most convenient CL system was found to be their reaction with ferrous gluconate in the presence of rhodamine 3B, which allowed the detection of up to 10 −9 M of diperoxides. The discovered CL-probe is selective towards tetraoxanes over reactive oxygen species such as singlet oxygen, hydroxyl radicals, hydrogen peroxide, hypochlorite and superoxide ions. It is suggested that electronically-excited states may be involved in biological activities of cyclic organic peroxides.